Knowledge of HIV/AIDS and attitudes towards people living with HIV among the general staff of a public university in Malaysia - Yvonne Tee; Mary Huang (Taylor & Francis Group, 2009)
Stigma and discrimination towards people living with HIV have been widely documented, and have extended their impact into the workplace. Stigmatising attitudes towards people living with HIV (PLHIV) in the workplace significantly hinder HIV prevention efforts and indirectly affect national development. This cross-sectional study was designed to determine the level of knowledge about HIV and AIDS and assess attitudes towards PLHIV among the general staff of Universiti Putra Malaysia (UPM), as well as to identify factors that are associated with it. Self-administered questionnaires were posted to a total of 344 general staff from six randomly selected faculties, and they were a given a week to return the questionnaires. The response rate was 38%. Data were analysed using Pearson's correlation, independent t-test and multiple linear regression. The respondents showed a considerably high level of knowledge about HIV/AIDS (mean knowledge score of 15.57±1.93 out of 18 points) although there were some misconceptions (N=129). Likert scale responses to 20 attitude statements revealed that respondents generally had moderately positive attitudes toward PLHIV (average score of 69.65±10.08 out of 100 points). Attitudes were inconsistent when it involved direct contact and interaction with PLHIV. Factors significantly associated with level of knowledge and attitudes included age, education and income. There was no difference in mean score for knowledge and attitudes by gender. Further efforts are necessary to improve attitudes of the general staff towards PLHIV, particularly in areas of direct contact with PLHIV.